2000
DOI: 10.1136/bjo.84.1.37
|View full text |Cite
|
Sign up to set email alerts
|

Coats' syndrome: long term follow up

Abstract: Aim-To increase the understanding of the long term results in pseudoretinoblastoma eyes with infantile Coats' syndrome. Methods-This study design was a retrospective case review. 10 patients were analysed who were initially referred with a diagnosis of retinoblastoma but had Coats' syndrome on the basis of ocular oncological evaluation. Vision, fundus photography, ultrasonography, and computed tomography scans were obtained and evaluated. Changes in vision and retinal status were measured. Results-The initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
15

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 19 publications
2
34
0
15
Order By: Relevance
“…1,7,[9][10][11] While previous studies have been Coats disease in the United Kingdom 1: epidemiology and presenting features B Morris et al enlightening they did not seem to reflect the cases of Coats disease we have typically encountered in clinical practise. On the other hand, the smaller numbers in our study could make the differences observed to be a chance rather than a real occurrence.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…1,7,[9][10][11] While previous studies have been Coats disease in the United Kingdom 1: epidemiology and presenting features B Morris et al enlightening they did not seem to reflect the cases of Coats disease we have typically encountered in clinical practise. On the other hand, the smaller numbers in our study could make the differences observed to be a chance rather than a real occurrence.…”
Section: Discussionmentioning
confidence: 90%
“…This difference may be because many younger children were referred to the ocular oncology at Wills Eye Hospital because of concern about possible underlying retinoblastoma by the referring doctor (27% of cases). 1 Indeed, in a different series of 10 children with Coats disease reported by Char 11 , and who were originally referred because of suspected retinoblastoma, the mean age at diagnosis was just 2.4 years (29 months).…”
Section: Age (Months)mentioning
confidence: 99%
“…[6][7][8] It is not surprising therefore that an examination under anaesthesia was performed in a significant proportion of cases (42%), and that ultrasound (26%) and FFA (35%) were also used extensively. Somewhat surprisingly in our series, in 18 cases (32.7%) no investigations were carried out in addition to the clinical examination.…”
Section: Discussionmentioning
confidence: 99%
“…El tratamiento óptimo en los casos de enfermedad de Coats que cursan con desprendimiento de retina sigue siendo incierto. Algunos autores han sugerido que la crioterapia resulta más efectiva en los casos más graves (4). La fotocoagulación con láser es efectiva solamente si la retina no se encuentra desprendida.…”
Section: Discussionunclassified